The Role of NLRP3 Inflammasome Signaling on Arrhythmias in Diabetes - Zhang L; Liu HH; Li F; Yang F; Qian LL; Wang RX (Dove Medical Press, 2022)
Lei Zhang,1,* Huan-Huan Liu,2,* Feng Li,1 Fan Yang,1 Ling-Ling Qian,1 Ru-Xing Wang1 1Department of Cardiology, Wuxi People's Hospital Affiliated to Nanjing Medical University, Wuxi, People's Republic of China; 2Wuxi School of Medicine, Jiangnan University, Wuxi, People's Republic of China*These authors contributed equally to this workCorrespondence: Ru-Xing Wang, Tel +86-510-85351593, Fax +86-510-85350555, Email ruxingw@aliyun.comAbstract: Diabetes is a significant risk factor for arrhythmias. However, the pathophysiology of diabetes-related arrhythmias still needs to be elucidated, presumably associated with structural and electrical remodeling. There is growing evidence that inflammation and arrhythmias are intimately associated, which has spurred significant interest in exploring the regulatory links in diabetes. Recent research findings have revealed a vital role for the NOD-like receptor family pyrin domain containing 3 (NLRP3) inflammasome signaling, and facilitated the occurrence of arrhythmias in diabetes, including NLRP3 inflammasome activation by multiple stressors and its downstream cytokines, interleukin-1β (IL-1β) and interleukin-18 (IL-18). This narrative review aims to summarize the complex interaction between NLRP3 inflammasomes signaling and diabetes-related arrhythmias. Articles regarding the role of NLRP3 inflammasome in diabetes-related arrhythmias and relevant mechanisms were selected. Relevant articles were selected from PubMed. The search terms were "NLRP3 inflammasome" and "diabetes" and "arrhythmia". Important references from selected articles were also retrieved. The role of NLRP3 inflammasome signaling in diabetes-induced arrhythmias may provide a new option for the prevention and treatment diabetes-related arrhythmias.Keywords: NLRP3, inflammasome, diabetes, arrhythmia